Peran moderasi good corporate governance pada hubungan corporate social responsibility dengan nilai perusahaan pertambangan yang terdaftar di Bursa Efek Indonesia - Susanti, Novita Dwi; Handayani, Susi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This purpose of this study to examine and analyze the moderating role of good corporate governance in the relationship between corporate social responsibility and the value of mining companies listed on the Indonesia Stock Exchange for the 2015-2020 period. The method in this study uses quantitative methods with secondary data obtained from www.idx.co.id and the official website of the sample company website. The independent variable of this research uses corporate social responsibility disclosure. The dependent variable used is the firm value proxied by Tobins q. the moderating variable is good corporate governance in the form of an independent board of commissioners. The analytical method used is Moderated Regression Analysis (MRA). The results showed that CSR had a significant effect on firm value and good corporate governance had a significant effect on the relationship between CSR and firm value.